Recurrent Duplication and Diversification of Acrosomal Fertilization Proteins in Abalone - Carlisle, J. A.; Glenski, M. A.; Swanson, W. J. (Frontiers in Cell and Developmental Biology, 2022)
Reproductive proteins mediating fertilization commonly exhibit rapid sequence diversification driven by positive selection. This pattern has been observed among nearly all taxonomic groups, including mammals, invertebrates, and plants, and is remarkable given the essential nature of the molecular interactions mediating fertilization. Gene duplication is another important mechanism that facilitates the generation of molecular novelty through functional divergence. Following duplication, paralogs may partition ancestral gene function (subfunctionalization) or acquire new roles (neofunctionalization). However, the contributions of duplication followed by sequence diversification to the molecular diversity of gamete recognition genes has been understudied in many models of fertilization. The marine gastropod mollusk abalone is a classic model for fertilization. Its two acrosomal proteins (lysin and sp18) are ancient gene duplicates with unique gamete recognition functions. Through detailed genomic and bioinformatic analyses we show how duplication events followed by sequence diversification has played an ongoing role in the evolution of abalone acrosomal proteins. The common ancestor of abalone had four members of its acrosomal protein family in a tandem gene array that repeatedly experienced positive selection. We find that both sp18 paralogs contain positively selected sites located in different regions of the paralogs, suggestive of functional divergence where selection acted upon distinct binding interfaces in each paralog. Further, a more recent species-specific duplication of both lysin and sp18 in the European abalone H. tuberculata is described. Despite clade-specific acrosomal protein paralogs, there are no concomitant duplications of egg coat proteins in H. tuberculata, indicating that duplication of egg proteins per se is not responsible for retention of duplicated acrosomal proteins. We hypothesize that, in a manner analogous to host/pathogen evolution, sperm proteins are selected for increased diversity through extensive sequence divergence and recurrent duplication driven by conflict mechanisms.